PATIENT ADAPTATION TO COMPLETE DENTURES: PROBLEMS AND SOLUTIONS (Eureka Journal of Physical and Chemical Research, 2026)
Adaptation to complete removable dentures represents a complex physiological and psychological process that significantly influences treatment success in edentulous patients. Despite advances in prosthodontic techniques, many patients experience discomfort, functional limitations, and emotional stress during the adaptation period. The purpose of this study is to analyze common adaptation problems associated with complete dentures and to identify effective clinical and behavioral strategies to improve patient outcomes. A clinical observational study combined with literature analysis was conducted involving edentulous patients receiving new complete dentures. Adaptation difficulties were evaluated through clinical examinations and patient-reported outcomes during a six-month follow-up period. The results demonstrate that most adaptation problems occur within the first weeks of denture use and include impaired mastication, speech difficulties, mucosal irritation, and psychological resistance. Appropriate prosthetic adjustments, patient education, and gradual neuromuscular training significantly improve adaptation.
Keywords: Complete dentures, patient adaptation, edentulism, prosthodontic rehabilitation, denture discomfort, neuromuscular adaptation, removable prostheses